Uma Implementação de Pontos de Testes Baseados em Pontos de Função Aplicados em um Órgão Público na Paraíba - Araújo, Jeremias; Lima, Carlos; Roberto, Ricardo (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2017)
The measure techniques based on function points are used as reference to measure effort and costs of a software development project, which is applied by private and public companies in several areas. In the current scenario in Court of Justice of Paraíba, the effort estimates of development are performed in all products, and function points analysis are used to conduct these estimates. Recently, the software testing team raised in court of justice of Paraíba and improved the product quality and the process itself. This paper aims an analysis, presentation and implementation of effort estimation by using function points, describing the collected outcomes and then ensuring a greater accuracy in the estimation of time and effort to achieve the test process activities keeping the quality of the results.